The Ruling on the Marriage of a Pregnant Woman from an Illegitimate Relationship: A Perspective from the Ulama Consultative Assembly of North Aceh Regency, Indonesia - Dastur, Muhammad; Ja'far, Ja'far; Bastiar, Bastiar; Noor, Umar Muhammad (STAI Serdang Lubuk Pakam, 2024)
This article examines the opinion of the North Aceh District Ulama Consultative Assembly (MPU) on the marriage of pregnant women outside of marriage. Although it is a field study, it first examines the fiqh perspective on the topic, and then reviews the MPU board's opinion on the topic. The study proposes the finding that in Islamic fiqh, the marriage of a pregnant woman out of wedlock is debated based on the cause of the pregnancy. The Maliki, Hanbali and Abu Yusuf (Hanafi) schools of thought reject the validity of the marriage of a pregnant woman resulting from adultery, while the Shafi'i and Abu Hanifah schools of thought consider it valid. However, the marriage of a pregnant woman is generally considered invalid during the 'iddah period if she is pregnant from a legal or illegal relationship. The MPU of North Aceh stated that the marriage of a pregnant woman out of wedlock is legally valid but haram, as it can lead to the uncertainty of the child's nasab. They recommend that such marriages be avoided to prevent potential problems with nasab and other rights. The implications of this study show the importance of harmonization between fiqh rules and the needs of contemporary society in marriage law, as well as the need for community education to prevent marriages that can cause social and legal problems.